ANALISIS YURIDIS TERBITNYA SERTIPIKAT HAK MILIK PADA TANAH GARAPAN YANG MASIH BERSTATUS HAK GUNA USAHA ( STUDI PADA PTPN III MEMBANG MUDA KABUPATEN LABUHAN BATU ) - RIRIN RISMAULI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhammad Yamin2. Syafruddin Kalo3. Hasim Purba PTPN III Membang Muda has been registered as the holder of HGU (leasehold) since December 23, 2005, based on the Directive of the Head of BPN (National Land Agency) No. 119/HGU/BPN/2005, and it will last until December 23, 2005, and it will be possibly renewed for 25 years. The problem is that a SHM (debenture) of the same land location in the name of HSN was issued by the Land Office on April, 2012. The research problems are how about the validity of registering HGU by PTPN III Membang Muda, how about the settlement of dispute attempted by PTPN III Membang Muda on the issuance of SHM on the HGU land of PTPN III Membang Muda, and how about the legal certainty on the issuance of SHM on the land located in PTPN III Membang Muda.Keywords : Land Registration, Debenture, Leasehold